A metaconceptual viewpoint in teaching about chemical bonds - Joki, Jarkko (LUMAT-B: International Journal on Math, Science and Technology Education, 2016)
In the research of chemistry education, it has been observed that using the octet rule in teaching about chemical bonds, often causes an alternative octet framework in students. It bothers the forming of a meaningful, explanatory power and a scientifically proper understanding of chemical bonds. Metaconceptualism is a part of metacognition. Increasing metaconceptual understanding in chemistry education helps students to perceive the nature of different concepts, models and schemes, its use and boundaries. This article considers the teaching of chemical bonds from a metaconceptual point of view.